COVID-19 evolution in China up to 14/04/2022 - Mora-Alvarado, Darner A. (2023)
The present study analyses the evolution of COVID-19 from its origin in Wuhan, China, by studying the data provided by virtual platforms to compare China situation with the world context up to 14/04/2022. In addition, four hypotheses of the origin of SARS-CoV-2 were addressed, according to the report of the World Health Organization (WHO) in February and March 2021 in Chinese territory. The progress in vaccination in the Chinese population was also determined, with the immunizers produced by Chinese scientists, which reached 88.02% as of 04/11/2022. In addition to this, the “zero tolerance” policy against COVID-19 was analysed. Finally, three scenarios were established: one positive, the second in the middle and the third catastrophic, so that the Chinese health authorities manage the future of the economic and social health crisis of COVID-19 in 2022 and 2023.